2017
DOI: 10.1364/jocn.9.0000b1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Performance of Spatially Joint-Switched Space Division Multiplexing Optical Networks via Spatial Group Sharing

Abstract: Space division multiplexing (SDM) is a promising approach to overcome the looming fiber capacity crunch. Joint and fractional joint switching (JoS and FJoS) architectures, which switch multiple spatial dimensions together as atomic units, have been proposed to reduce the cost of implementing SDM and cater to strongly coupled transmission media. However, they have been shown to impose significant penalties to overall network performance, at least when many relatively small connections are used in the context of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…In [16], we further showed that SG-Sw paradigms with lower G values perform well for networks with high level of traffic diversity, while J-Sw is favorable for networks with large demands. In addition, in [17], several algorithms have been proposed to improve the performance of different SDM switching paradigms when uncoupled fibers are in place. Note that in [15] [16], Ind-Sw, J-Sw and FrJ-Sw with G = 3 were only examined with a fixed spectral channel width (ChBW)defined as the spectrum over each of the spatial dimensions used to allocate the spatial Sp-Ch constituents-equal to 50 GHz.…”
Section: Related Work and Novelty Of The Papermentioning
confidence: 99%
“…In [16], we further showed that SG-Sw paradigms with lower G values perform well for networks with high level of traffic diversity, while J-Sw is favorable for networks with large demands. In addition, in [17], several algorithms have been proposed to improve the performance of different SDM switching paradigms when uncoupled fibers are in place. Note that in [15] [16], Ind-Sw, J-Sw and FrJ-Sw with G = 3 were only examined with a fixed spectral channel width (ChBW)defined as the spectrum over each of the spatial dimensions used to allocate the spatial Sp-Ch constituents-equal to 50 GHz.…”
Section: Related Work and Novelty Of The Papermentioning
confidence: 99%
“…UFRs are considered simply as a set of independent SMF whose nonlinear impairments are the same of single SMF and where independent switching (InS) [44] can be implemented. Here, however, we will apply the core continuity constraint (CCC) [45] switching technique also in UFRs.…”
Section: Networking With Different Sdm Solutionsmentioning
confidence: 99%
“…The SNR improvement from NLM ∆SNR is derived according to the theory as [47]. However, SCMCFs require joint switching (JoS) implementation [44] due to the strong core coupling. This means that the add/drop of a channel and the LP allocation on a particular wavelength must be done on the same route and in all the cores [46,47].…”
Section: Networking With Different Sdm Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the traffic profile, it has been demonstrated that JoS performance can be significantly worse than that of InS 8 due to its spectrum wastage. In order to enhance it, some strategies have been proposed 6,9 . For example, e2e-grooming aims to reuse lightpaths for other demands having common source (s) and destination (t) nodes, always targeting a minimization when allocating them.…”
Section: End-to-end Spatial Traffic Groomingmentioning
confidence: 99%